Work in IT for women: The realities of Ukraine - Petryshchenko, Nataliia; Azhaman, Iryna; Serohina, Nataliia (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article presents a study conducted on gender equality in Ukraine in the field of information technology. The problem of gender inequality still exists throughout the world. The purpose of the article is to study the working conditions of women in IT, to discuss the possible use of stereotypes, and to identify the reasons for women’s lack of interest in working in this field. Formally, there is no prohibition for women to work in the IT industry. However, there are a number of reasons in Ukraine that affect the possibilities of pursuing a career in this direction. The article analyzes the available statistical data and the results of a survey among representatives of the IT sector. It is worth noting the problem of data collection during the war in Ukraine. The importance of the sphere for the country’s economy as a whole and the relevance, demand for specialists, as well as the ratio of women and men employed in this area are considered. Global trends in gender distribution in the field of IT were analyzed. The main stereotypes and situations that constitute obstacles for women in this area are considered and the features inherent in Ukrainian society are also highlighted. Based on the statistical data of Ukraine the number and structure of female students, including foreigners, in recent years were analyzed. It was revealed that the structure of the gender ratio of men and women in education is changing with the formation of the labor market of Ukraine and the distribution by employment status. The ratio of working women and men is approximately the same, but the structure by employment status is different. In Ukraine the IT sector is largely based on individual entrepreneurs. Despite the martial law, the IT community is actively developing and new companies are being created. Training is actively carried out in paid and free courses. Surveys were conducted among students, and it was found that the beginning of a career in the field of information technology is already determined by certain stereotypes of society. Based on the conducted research, the structural gender relations in the field of IT and the main stereotypes that hinder the development of women in this area are analyzed. Recommendations for overcoming gender inequality in the field of IT in Ukraine are presented. Based on the information received, conclusions were drawn: the number of women and men studying technical and mathematical sciences in Ukraine is approximately the same. But in the future, in professional activities, women in many cases prefer to occupy weaker positions, leaving leading positions to men. The main reason for this dynamic is the generally accepted stereotypes and the actualization of the role of women in other areas.
Keywords: gender equality; IT in Ukraine; career of women in IT; stereotypes for women; public support